Distended diameter of the inferior vena cava is suggestive of pulmonary thromboembolism on unenhanced post-mortem CT. Issue 1 (March 2015) - Mueller, S.L.; Thali, Y.; Ampanozi, G.; Flach, P.M.; Thali, M.J.; Hatch, G.M.; Ruder, T.D.
Abstract Introduction Cases of fatal pulmonary embolism (PE) represent a diagnostic challenge on post-mortem imaging. The aim of this study was to investigate the correlation between distended inferior vena cava (IVC) on post-mortem CT (PMCT) and PE at autopsy. Materials and methods We retrospectively measured the diameter of the IVC at the origin of the superior mesenteric artery in 164 cases on PMCT. Thereof 26 cases with PE, 24 selected control cases with myocardial infarction (MI), and 114 randomized control cases were investigated. Results Mean IVC diameters were 11.2 mm in the PE group; 7.4 mm in the MI group; and 6.7 mm in the randomized control group. Mean IVC diameters in the PE group were significantly wider than in the randomized control group (p=0.004), but not significantly wider than in the MI group (p=0.111). The difference between the IVC diameters of both control groups was also not significant (p=0.400). Receiver operating characteristics (ROC) curve revealed that the optimal cut-off value was at an IVC diameter of 12.5 mm, which indicates the presence of pulmonary artery embolism with a sensitivity of 54% and a specificity of 83%. Conclusions This study revealed that increased diameter of the inferior vena cava is suggestive of pulmonary embolism on PMCT. However, other causes of right heart failure may also cause distension of the inferior vena cava. Further research is needed to enable a reliable distinction between cases of PE and MI.